Angiogenic Factors and Preeclampsia with Severe Features Among a Primarily African American Cohort [21C]. (May 2018) - Perdigao, Joana; Minhas, Ruby; Chintala, Sireesha; Mueller, Ariel; Young, Danielle; Rana, Sarosh
Abstract : INTRODUCTION: Preeclampsia related morbidity and mortality is rising predominantly due to delayed identification of patients at risk for severe features (preE-SF). This study explored the association between angiogenic biomarkers (sFlt and PlGF) and preE-SF. METHODS: Women with hypertensive disorders of pregnancy (HDP) were enrolled upon admission. Blood samples were collected within 96 hours of delivery. Angiogenic markers were measured on an automated platform. Severe disease was defined by ACOG criteria as BP ≥160/110, thrombocytopenia, right upper quadrant pain/epigastric pain/transaminases, renal insufficiency, pulmonary edema, or cerebral/visual disturbances. Descriptive statistics were assessed with a Wilcoxon Rank Sum, chi-square or Fisher's exact test, as appropriate. Univariate and multivariable logistic regression was used to assess for differences in outcomes and angiogenic markers were assessed in tertiles. RESULTS: Our study included 375 women with HDP, of which 127 (33.9%) had preE-SF, 115 (30.7%) had gestational hypertension, and 66 (17.6%) had chronic hypertension. Our cohort was predominantly African American (74.4%). Levels of sFlt1 (pg/ml) were significantly higher in women with severe features compared to those without (9372.5 vs. 3607.0; p<0.0001), while levels of PlGF (pg/ml) were lower (51.0 vs. 122.0; p<0.0001) and the ratio of sFlt1/PlGF was significantly higher (212.0 vs. 32.0, p<0.0001). The highest tertile of sFlt1/PlGF was strongly associated with preE-SF (OR 9.05, 95% CI: 4.25-19.24; p<0.0001) in multivariable analysis. CONCLUSION: This study demonstrates a significant association between an abnormal angiogenic profile and preE-SF in a primarily African American cohort. Additional evaluation of the role of angiogenic markers during assessment for HDP and disease severity is needed.